Polymeric Micelles: A Promising Pathway for Dermal Drug Delivery - Parra, Ana (2021)
Nanotechnology is an area in great development and with application in the most varied fields of science, including cosmetic and pharmaceutical industries. Because conventional formulations for topical application are not always able to effectively penetrate the physical barrier that human skin exerts against factors and compounds of the external environment, polymeric micelles appear as alternative carriers for drugs and active ingredients delivery, also allowing ingredients with lower solubility and higher lipophilicity to be delivered. In fact, the augmented bioavailability of drugs, greater efficacy even at a lower dose, and selective drug delivery in specific organelles are very interesting advantages of the polymeric micelles usage in cutaneous application. As a consequence, they show a reduction in many of the local and systemic adverse effects, which might lead to an increase in patient compliance to the therapeutics, constituting a promising alternative to conventional topical formulations. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.